2022
DOI: 10.1038/s41418-022-01058-0
|View full text |Cite
|
Sign up to set email alerts
|

Sub-lethal signals in the mitochondrial apoptosis apparatus: pernicious by-product or physiological event?

Abstract: One of the tasks of mitochondria is the rule over life and death: when the outer membrane is permeabilized, the release of intermembrane space proteins causes cell death by apoptosis. For a long time, this mitochondrial outer membrane permeabilization (MOMP) has been accepted as the famous step from which no cell returns. Recent results have however shown that this quite plainly does not have to be the case. A cell can also undergo only a little MOMP, and it can efficiently repair damage it has incurred in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 99 publications
2
12
0
Order By: Relevance
“…We focused on the intrinsic pathway of apoptosis, by which cell death normally occurs in response to persistent intracellular stresses. [69][70][71] Consistent with the relatively muted signaling of this pathway relative to, for example, pyroptosis, we found that the apoptosome lacks supersaturable DFDs (Figure S5A).…”
Section: Supersaturation Drives Signal Amplification In Human Cellssupporting
confidence: 69%
“…We focused on the intrinsic pathway of apoptosis, by which cell death normally occurs in response to persistent intracellular stresses. [69][70][71] Consistent with the relatively muted signaling of this pathway relative to, for example, pyroptosis, we found that the apoptosome lacks supersaturable DFDs (Figure S5A).…”
Section: Supersaturation Drives Signal Amplification In Human Cellssupporting
confidence: 69%
“…Many proinflammatory pathways occur during mitochondrial outer membrane permeabilization, a critical factor in cell death during mitochondrial apoptosis. Recent studies are consistent with sublethal signaling in the mitochondrial apoptotic pathway driving inflammation, the first step in the immune response [112] …”
Section: Inflammation Dna Damage and Mitochondrial Imbalancesupporting
confidence: 59%
“…Recent studies are consistent with sublethal signaling in the mitochondrial apoptotic pathway driving inflammation, the first step in the immune response. [112] Infiltrated mitochondria trigger inflammation partly by releasing mitochondria-derived damage-associated molecular patterns (DAMPs). As DAMPs, histones are a class of endogenous molecules that trigger the immune response by directly interacting with the cell membrane and activating pattern recognition receptors.…”
Section: Inflammation Dna Damage and Mitochondrial Imbalancementioning
confidence: 99%
“…IAPs are also crucial regulators of inflammatory pathways because they influence both the activation of inflammatory genes and the induction of cell death through the receptorinteracting serine-threonine protein kinases (RIPKs), nuclear factor κB (NF-κB)-inducing kinase, and mitogen-activated protein kinases (MAPKs). Several studies have revealed an anti-inflammatory potential of RIPK inhibitors that either block inflammatory signaling or block the form of inflammatory cell death known as necroptosis [37,38]. There are several endogenous inhibitors of death that protect cells from programmed death.…”
Section: Apoptosis-mitochondria Interactionmentioning
confidence: 99%

Is death a living being?

Abdelrazak Mansour Ali,
Radwa Abdelrazak Ali,
Ahmed Abdelrazak Ali
2023
Int. J. Sci. Technol. Res. Arch